2015
DOI: 10.1117/1.jbo.20.7.076005
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved microscopy reveals the driving mechanism of particle formation during ultrashort pulse laser ablation of dentin-like ivory

Abstract: In dental health care, the application of ultrashort laser pulses enables dental tissue ablation free from thermal side effects, such as melting and cracking. However, these laser types create undesired micro- and nanoparticles, which might cause a health risk for the patient or surgeon. The aim of this study was to investigate the driving mechanisms of micro- and nanoparticle formation during ultrashort pulse laser ablation of dental tissue. Time-resolved microscopy was chosen to observe the ablation dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…In contrast, the ultimate tensile strength of kidney stones is only in the order a few MPa and gall stones should have similar mechanical properties. Because of their structural similarity , it is expected that dentin shows nearly the same ablation behavior as the mammoth ivory while the other samples may show however different behaviors regarding photomechanical ablation.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the ultimate tensile strength of kidney stones is only in the order a few MPa and gall stones should have similar mechanical properties. Because of their structural similarity , it is expected that dentin shows nearly the same ablation behavior as the mammoth ivory while the other samples may show however different behaviors regarding photomechanical ablation.…”
Section: Methodsmentioning
confidence: 99%
“…Time‐resolved investigations of the femtosecond‐laser‐induced ablation dynamics of dentin‐like mammoth ivory in the top view perspective revealed that material removal is based on the combination of 2 mechanisms . The first mechanism was found to be similar to the ablation of dielectrics: multiphoton absorption and avalanche ionization cause laser‐induced breakdown in the excited region , and expansion of the generated plasma leads to material removal.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations